Kodin älylaitteet teknostressin aiheuttajina - Rossi, Karoliina (2024)
The use of technology outside work is on the rise, and smartphones play a big role in this today. Housing is also changing towards a techno filled everyday life and comfort is taking on a new level. Smart devices in a co-environment, such as robotic vacuum cleaners, bring ease and fluidity to everyday life, but the downside is that technology and its use also bring challenges. The aim of this thesis was to answer the question of what kind of technostress smart ho-me devices cause and why. Smart home devices were limited to household appliances such as robotic vacuum cleaners or surveillance cameras. Smartphones and tablets were not included in the survey. The study sought to identify the technostressors that interviewees face in their daily lives when using smart appliances. The empirical data for the study was collected through thematic interviews with people who had negative experiences of using smart home devices. Qualitative methods were used to process the data. The results showed that smart devices in the home cause technostress when they do not work. Among the factors causing technostress, the most fre-quently observed was the unreliability of the devices. Unreliability was expe-rienced because the devices did not work as they should have done. Techno-invasion was observed in several interviews and resulted in interruptions in the performance of everyday tasks. Although smart devices in the home caused negative emotions, there was no desire to give them up because they made everyday life easier. The most common emotions were irritation and frustration. This thesis provides a new insight into the study of technostress in the leisure context of the home.